Double-edged functions of hemopexin in hematological related diseases: from basic mechanisms to clinical application - Li, Yijin; Chen, Renyu; Wang, Chaofan; Deng, Jun; Luo, Shanshan (Frontiers in Immunology, 2023)
It is now understood that Hhemolysis and the subsequent release of heme ininto circulation isplay a crucial impetus forcritical role in driving the progression of various diseases. Hemopexin (HPX) is), a heme-binding protein with the highest affinity tofor heme in the plasma and, serves as an efficienteffective antagonist ofagainst heme toxicity induced by resulting from severe acute or chronic hemolysis. ChangesIn the present study, changes in theHPX concentration were characterized of HPX inat different stages of hemolytic diseases were characterized, giving credit to HPX for being, underscoring its potential as a biomarker infor assessing the progressdisease progression and prognosis of these diseases. Endogenous HPX is usually insufficient to provide protection against. In many heme overload-driven diseaseconditions, such as sickle cell disease, transfusion-induced hemolysis, sepsis, etc. As a result, increasingand sepsis, endogenous HPX levels are often insufficient to provide protection. Consequently, there is growing interest has been diverged to developin developing HPX therapeutics to targetmitigate toxic heme exposure. SupplementStrategies include HPX supplementation patients with HPX when endogenous HPX is exhaustedlevels are depleted and endow HPX with multiple functionsenhancing HPX's functionality through modification are considered a powerful weaponmodifications, offering a potent defense against heme-toxicity. Meanwhile, HPX mediatedIt is worth noting that HPX may also exert deleterious effects were also reported under certain circumstances. This review aims to provide an integrativea comprehensive overview on theof HPX's roles of HPX in in the progression and prognosis of hematological related disease progression and prognosis,diseases. It highlights HPX-based clinical therapies against distinctfor different hematological disorders, updates novel technologydiscusses advancements in HPX production and modification, hopefully provides technologies, and offers a theoretical basisbasis for the clinical application of HPX based on the data from relevant studies.